Integrasi Etika dan Keberlanjutan dalam Strategi Bisnis Modern - Takwa, Muhammad; Sikki, Nurhaeni; Mubarok, Rizqi; Bakri, Ayu Hartati; Majid, Muhammad Indra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
In the era of rapid globalization, digital transformation, and rising stakeholder expectations, the integration of ethics and sustainability into modern business strategy has become a critical determinant of long-term organizational resilience. This study provides a comprehensive literature review to examine how ethical principles and sustainability frameworks contribute to corporate performance, risk management, and stakeholder trust. Drawing upon recent academic sources, the study highlights the increasing relevance of Environmental, Social, and Governance (ESG) indicators, the Triple Bottom Line approach, and ethical leadership in shaping responsible business practices. Findings show that organizations embedding ethical values—such as transparency, accountability, and social responsibility—tend to cultivate stronger employee engagement, enhance brand legitimacy, and achieve superior long-term profitability. Moreover, sustainability-driven innovation, including green technologies and circular economy practices, plays a crucial role in strengthening competitive advantage in a dynamic market environment. However, the literature also reveals persistent challenges, such as greenwashing behaviors, misalignment between ethical commitments and operational practices, and internal resistance to organizational change. These issues underscore the need for authentic leadership, measurable sustainability indicators, and governance systems grounded in integrity. The study concludes that integrating ethics and sustainability is not merely a voluntary initiative but a strategic necessity for businesses seeking to thrive in a complex and rapidly evolving global landscape. By aligning economic goals with societal and environmental responsibility, companies can build a more sustainable and ethically grounded future.